2022
DOI: 10.3389/fpubh.2022.914417
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding “New Normal” Guidelines and Quality of Life Among Thai People During the COVID-19 Outbreak: An Online Cross-Sectional Survey

Abstract: In Thailand, strict prevention and control strategies have been implemented to mitigate the rapid spread of coronavirus disease 2019 (COVID-19). “New normal” guidelines and a series of mobile health applications have been introduced by the healthcare sector and implemented to aid the disease control monitoring and prevention of widespread outbreaks. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding “new normal” guidelines and quality of life (QOL) among Thai people during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…The finding on attitude levels showed that poor levels of COVID-19 attitude among Thai residents were found in risk perception and mistrust issues. This is in contrast with another study [33] that mentioned better attitudes regarding the "new normal" guidelines among Thai people during the COVID-19 outbreak. However, the study of Kunno et al [34] found that the level of good (50.9%) and poor (49.1%) attitudes toward COVID-19 among healthcare workers in the urban community of Bangkok, Thailand, were approximated.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The finding on attitude levels showed that poor levels of COVID-19 attitude among Thai residents were found in risk perception and mistrust issues. This is in contrast with another study [33] that mentioned better attitudes regarding the "new normal" guidelines among Thai people during the COVID-19 outbreak. However, the study of Kunno et al [34] found that the level of good (50.9%) and poor (49.1%) attitudes toward COVID-19 among healthcare workers in the urban community of Bangkok, Thailand, were approximated.…”
Section: Discussioncontrasting
confidence: 93%
“…The income variable of residents was significantly associated with COVID-19 preventive behaviors in this research, consistent with various studies [33,43]. Income levels are closely related to the preventive behavior of infectious diseases, and higher-income residents can obtain better and more accurate health information than their counterparts [43].…”
Section: Discussionsupporting
confidence: 90%
“…Knowledge about COVID-19 also influenced COVID-19 preventive behaviors among the people of working age in this study. We discovered that the working-age population had high levels of knowledge about COVID-19, suggesting that knowledge about COVID-19, particularly among working-age Thais, is crucial for combating the COVID-19 pandemic [ 4 , 11 , 27 ]. Consistent with prior research, our findings indicated a positive correlation between COVID-19 knowledge and COVID-19 preventive behaviors [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, confirmed cases and death rates in Thailand continue to increase, especially in crowded areas (e.g., large cities). Thai people have altered their actions and lifestyle choices to avoid contracting COVID-19 in what has been termed the “new normal”, which may be necessary to stop COVID-19 from emerging again in subsequent outbreaks and causing new COVID-19 pandemic waves [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies on the QOL in Thailand mostly fall into one of two categories: qualitative or quantitative (e.g., Jongudomkarn & Camfield, 2006;Kittipichai et al, 2015;Saladyanant et al, 2021;Tamornpark et al, 2022;Thongsing et al, 2020;Vutyavanich et al, 2007;Waewwab et al 2022;Yodmai et al, 2021), there are some exceptions (e.g., Mormon et al, 2021;Pheap & Sripokangkul, 2017). Our study uses both quantitative and qualitative methodologies to examine quality of life across a number of domains.…”
Section: Introductionmentioning
confidence: 99%